2020
DOI: 10.21203/rs.3.rs-19878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of MYB transcription factor gene ZmMYB59 affects seed germination in Nicotiana tabacum and Oryza sativa

Abstract: Background MYB transcription factors are involved in many biological processes, including metabolism, development and responses to biotic and abiotic stresses. In our previous work, a new MYB transcription factor gene, ZmMYB59 was induced by deep sowing and down-regulated during maize seed germination via Real-Time PCR. However, there are few reports on seed germination regulated by MYB proteins and the functions of ZmMYB59 remain unknown. Results In this study, to examine its functions, Agrobacterium -mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In previous studies, MYB TFs have been found to be closely related to seed germination. Specifically, AtMYB44, AtMYB96, and ZmMYB59 play a negative regulatory role in seed germination (Nguyen et al, 2012;Lee and Seo, 2015;Zhai et al, 2020). In this study, we found that the expression of PpMYB52 was maintained at a high level in the endodormancy stage, continued decrease throughout bud break, and decreased to the lowest level before bud break (Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In previous studies, MYB TFs have been found to be closely related to seed germination. Specifically, AtMYB44, AtMYB96, and ZmMYB59 play a negative regulatory role in seed germination (Nguyen et al, 2012;Lee and Seo, 2015;Zhai et al, 2020). In this study, we found that the expression of PpMYB52 was maintained at a high level in the endodormancy stage, continued decrease throughout bud break, and decreased to the lowest level before bud break (Figure 2B).…”
Section: Discussionmentioning
confidence: 52%
“…In wheat, dormancy release was shown to occur earlier after the TaMyB10-A1 gene was mutated (Mares and Himi, 2021). In maize, ZmMYB59 plays a negative regulatory role in germination (Zhai et al, 2020). Studying tomato, Xu et al (2018) found that overexpression of SlMYB102 can improve the seed germination rate.…”
Section: Introductionmentioning
confidence: 99%